Measurement of Posture in Children Aged 4-6 Years at Aisyah Makam Haji 1 Kartasura Kindergarten - Naufal, Adnan Faris; Deistriany, Zehra Karil; Prasetyani, Marlita; Putri, Nuristiqomah Dwi; Azizi, Laili Rahmawati; Azizah, Hauna Nur (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
Health screening is a form of monitoring children's growth and development, which involves evaluating growth and development status based on weight gain and addressing problems that may arise at each stage of a child's development. Physical health is measured by age, weight and height. The importance of conducting health checks on children early on is a crucial effort in detecting and preventing various health problems that may arise, including the problem of poor posture better known as bad posture. Bad posture is a condition in which the body's position deviates from the normal state which can cause various health problems. The possible negative consequences of bad posture include problems such as kyphosis, lordosis and scoliosis. Regular health checks on children, especially at early developmental stages such as in kindergarten, are important to identify early any potential health problems, including posture problems. By detecting such problems early, preventive measures can be taken immediately to avoid potentially more serious long-term impacts on children's health. Therefore, regular health check-ups in children are a necessity that cannot be ignored to maintain the health and well-being of future generations. In realizing the research results with quantitative methods, measurable and numerical-based data collection is involved to gain a deeper understanding of the posture characteristics of children in that age range. This provides a solid foundation for implementing appropriate preventive and posture corrective measures. The conducted research revealed intriguing findings regarding the posture of children at Aisyah Makam Haji 1 Kartasura Kindergarten. Among the observations: 56% of children were underweight, 10 children exhibited low arches on both feet, and 22% showed signs of scoliosis with a vertebral curve of 0°. While most children displayed normal limb length differences, some exhibited abnormalities in this aspect. These findings underscore the significance of posture screening for children aged 4-6 years, even if they seem physically healthy. Preventive measures, such as education for parents, are needed to prevent postural disorders that could potentially arise in the future.